Review on Heavy Metals Content in Sediment of Makasar Straits (1999, 2003, and 2004) - Helfinalis; Edward; Witasari, Yunia (Research Advances in Environment, Geography and Earth Science Vol. 7, 2024)
Measurements of heavy metal content in sediments in the Makassar Strait were carried out together with the Baruna Jaya VIII expedition in Indonesian waters in the study of marine biodiversity in August-September 1999, October 2003 and September-October 2004. Heavy metals measured were Pb, Cd, Cu, Zn, Cr and Ni. Sediment samples were taken using gravity piston cores at 12 research stations. Measurement of heavy metal levels was carried out using the Atomic Absorption Spectrophotometer (AAS). The purpose of this study was to evaluate the level of pollution and heavy metal contamination in sediments in the Makassar Strait. The results showed that the six heavy metals were still in accordance with the threshold value of the importance of marine biota. Based on the value of the contamination factor (CF), geoaccumulation index (I_geo) and pollution load index (PLI), the sediment in these waters is included in the category of not polluted and is still safe for marine biota (CF<0, I_geo<0 and PLI<1). The results of this study show that the parairan of the Makassar Strait is very good for habitat sustainability and diversity of marine life.